Making sense of humanity and other philosophical papers, 1982-1993 - Williams, Bernard, 1929-2003. (Cambridge [England] ; New York : Cambridge University Press, 1995)
This new volume of philosophical papers by Bernard Williams is divided into three sections: the first Action, Freedom, Responsibility, the second Philosophy, Evolution and the Human Sciences; in which appears the essay which gives the collection its title; and the third Ethics, which contains essays closely related to his 1983 book Ethics and the Limits of Philosophy. Like the two earlier volumes of Williams's papers published by Cambridge University Press, Problems of the Self and Moral Luck, this volume will be welcomed by all readers with a serious interest in philosophy. It is published alongside a volume of essays on Williams's work, World, Mind, and Ethics: Essays on the Ethical Philosophy of Bernard Williams, edited by J.E.J. Altham and Ross Harrison, which provides a reappraisal of his work by other distinguished thinkers in the field.
1. How free does the will need to be? -- 2. Voluntary acts and responsible agents -- 3. Internal reasons and the obscurity of blame -- 4. Moral incapacity -- 5. Acts and omissions, doing and not doing -- 6. Nietzsche's minimalist moral psychology -- 7. Making sense of humanity -- 8. Evolutionary theory and epistemology -- 9. Evolution, ethics, and the representation problem -- 10. Formal structures and social reality -- 11. Formal and substantial individualism -- 12. Saint-Just's illusion -- 13. The point of view of the universe: Sidgwick and the ambitions of ethics -- 14. Ethics and the fabric of the world -- 15. What does intuitionism imply? -- 16. Professional morality and its dispositions -- 17. Who needs ethical knowledge? -- 18. Which slopes are slippery? -- 19. Resenting one's own existence -- 20. Must a concern for the environment be centred on human beings? -- 21. Moral luck: a postscript.
Includes bibliographical references and index.
Keywords: Ethics; Human beings; Philosophy; Philosophy; Ethics; Humans; Philosophy